IMAGES OF RURAL LIFE IN MODERN CHINESE GENRE PAINTING - Фей, Мінкай (Art and Design, 2023)
The purpose of the article is to understand the stylistic, compositional and coloristic solutions of creating the image of rural life in modern genre painting of China. The research methodology is based on the use of both general scientific methods of analysis and special art-scientific methods, namely: methods of formal-stylistic and compositional-coloristic analysis. On the examples of the analysis of the paintings of Xin Dongwan, Chen Lizhong, Guo Beiping, and Li Zeping, the artistic features of the embodiment of images of rural life in modern genre painting of China are revealed. The main motifs of paintings about rural life in modern Chinese easel painting are revealed. The stylistic, compositional and coloristic solutions of creating images of rural life in modern genre painting of China are understood, and it is proved that the main stylistic direction of the representation of images of rural life is realism, a style that supports or restores referential connections with reality, with the culture of everyday life in China. Various approaches to the reflection of the contents of images of rural life in modern genre painting of China are characterized. It has been proven that the images of rural life in modern genre painting of China are a significant segment of its image that reflects the present. For the first time, the artistic features of the embodiment of images of rural life in modern genre painting of China are defined using the examples of paintings by Xin Dongwan, Chen Lizhong, Guo Beiping, and Li Zeping, created at the end of the 20th and beginning of the 21st centuries. The practical significance of the obtained results lies in the possibility of their application for professional art education both in Ukraine and in China. The study opens the perspective of studying other images of everyday life in modern Chinese genre painting.